(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Djatmiko HA, Kurniawan DW, Prihatiningsih N. 2022. Potential of Bacillus subtilis potato isolate as biocontrol agent of Xanthomonas oryzae pv. oryzae and candidate for nanosuspension formula. Biodiversitas 23: 3313-3317. Bacillus subtilis potato isolate was able to be an antagonist of plant pathogens. The aims of this study were (i) to examine the potential of potato isolate B. subtilis as a control for Xanthomonas oryzae pv. oryzae (Xoo) as a pathogen rice bacterial leaf blight, (ii) determine the inhibition mechanism of their isolates, (iii) evaluate the best B. subtilis to make nanosuspension formula. The method was carried out in a completely randomized design with 5 treatments of B. subtilis potato isolates B46, B209, B211, B298, and B315, repeated 4 times. Xoo and five B. subtilis were grown in nutrient broth medium in a shaker. Xoo and B. subtilis were grown in yeast peptone glucose agar medium by the diffusion method. Xoo was inoculated on medium, and then a 5 mm diameter filter paper immersed with B. subtilis suspension was placed on the medium. The best B. subtilis as a controller was used to formulate into nanosuspension. The variables were zone of inhibition, inhibition mechanism and antibiosis index. The results showed that only three B. subtilis were able to inhibit the growth of Xoo, namely B211, B298 and B315 isolates. The highest (10 mm) inhibition zone was recorded by B. subtilis B315 isolate. The mechanism of inhibition of the three isolates of B. subtilis against Xoo was bacteriostatic. The antibiosis index of B. subtilis B315 against Xoo was 1 (strong). The selected B. subtilis B315 was developed as a nanosuspension formula with inhibition zone of 2.1 mm and antibiosis index was 0.42.